Uretero-Internal Pudendal Artery Fistula with Longterm Indwelling of Ureteral Stent: A Case Report - Hideo Yuki; Yasuhiro Takayama; Masahisa Takuma; Mika Takahashi; Tadasuke Ando; Yasuhiro Sumino; Takeo Nomura; Fuminori Sato; Hiromitsu Mimata (Case Reports in Medicine)
A 74-year-old woman presenting with bilateral ureteral stricture was referred to our hospital. She had undergone radical hysterectomy and adjuvant irradiation therapy for cervical cancer in 2000. Double-J stents were inserted in both the ureters and replaced at regular intervals. Eighteen months after ureteral stenting, she complained of gross hematuria and was managed with hemostatic agents. During a routine replacement of the right double-J stent, massive bleeding was observed from the urethra which continued intermittently. The source of bleeding was not identified on computed tomography and angiography. We kept her at rest, which reduced the bleeding. However, she required intermittent transfusions. Angiography was performed at the time of bleeding on March 5, 2011. A uretero-internal pudendal artery fistula was found, and coil embolization was performed. Thereafter, hematuria did not recur up to the last followup in July 2011.